2003
DOI: 10.1021/bi026995a
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Molecular Components of Calcium Transport Regulation in a Reconstituted Membrane System

Abstract: Using a chemically defined reconstitution system, we performed a systematic study of key factors in the regulation of the Ca-ATPase by phospholamban (PLB). We varied both the lipid/protein and PLB/Ca-ATPase ratios, determined the effects of PLB phosphorylation, and compared the regulatory effects of several PLB mutants, as a function of Ca concentration. The reconstitution system allowed us to determine accurately not only the PLB effects on K(Ca) (Ca concentration at half-maximal activity) of the Ca-ATPase, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
84
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(105 citation statements)
references
References 61 publications
18
84
3
Order By: Relevance
“…We also confirmed that PLB molecules of normal inhibitory strength (N30C-PLB) do not significantly affect the V max of the Ca 2ϩ -ATPase (1). This is contrary to conclusions of several recent studies in which PLB was reported to either decrease (22) or increase (20,21,23) the V max of the Ca 2ϩ -ATPase. Using our viral constructs and the 2D12 antibody, Waggoner et al (22) recently noted a modest reduction (ϳ20%) in the V max of SERCA2a co-expressed with wild-type PLB compared with SERCA2a expressed alone.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We also confirmed that PLB molecules of normal inhibitory strength (N30C-PLB) do not significantly affect the V max of the Ca 2ϩ -ATPase (1). This is contrary to conclusions of several recent studies in which PLB was reported to either decrease (22) or increase (20,21,23) the V max of the Ca 2ϩ -ATPase. Using our viral constructs and the 2D12 antibody, Waggoner et al (22) recently noted a modest reduction (ϳ20%) in the V max of SERCA2a co-expressed with wild-type PLB compared with SERCA2a expressed alone.…”
Section: Discussioncontrasting
confidence: 99%
“…4B). The studies in which wild-type PLB and some other PLB mutants were reported to actually increase the V max of the Ca 2ϩ -ATPase were all conducted with the purified rabbit skeletal muscle enzyme co-reconstituted with purified PLB from detergent solution (20,21,23). In this case, it is possible that enzyme protection by PLB during the reconstitution process may have artifactually affected the results, as was recently suggested (23).…”
Section: Discussionmentioning
confidence: 99%
“…PLN variants were coreconstituted with purified SERCA (46,47) in lipid bilayer membranes (1,2-dioleoyl-sn-glycero-3-phosphocholine: 1,2-dioleoyl-sn-glycero-3-phosphoethanolamine, DOPC:DOPE, 4∶1) at molar ratios of 10∶1 PLN:SERCA and 700∶1 lipids:SERCA. The Ca 2þ dependence of the ATPase activity was measured using a coupled enzyme assay at 37°C (48) and monitored as for the PKA-C assays.…”
Section: Methodsmentioning
confidence: 99%
“…The Ca 2þ dependence of the ATPase activity was measured using a coupled enzyme assay at 37°C (48) and monitored as for the PKA-C assays. Initial rates of SERCA was measured as a function of calcium concentration (pCa), and data were fit to the Hill equation (48).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the residue changes at these two positions (Tyr 6 to His and Leu 7 to Met) account for the functional consequences of the zfHEAD chimera. The effect of PLN on the maximal activity of SERCA is only observed at high protein to lipid and PLN to SERCA ratios that mimic cardiac SR membranes (36,47), and this effect is not reversed by PKA-mediated phosphorylation (30). Residues that contribute to the V max stimulation of SERCA are found in the cytoplasmic and transmembrane domains of PLN (30,36,37).…”
Section: Discussionmentioning
confidence: 99%